EVALUASI PEMBELAJARAN UJIAN AKHIR SEMESTER MATA PELAJARAN BISNIS ONLINE KELAS XII SMK SUNAN DRAJAT LAMONGAN - Miftachul Ulum; Abdul Mun’im; Erly Juliyani; Pusvyta Sari (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
At the end of each semester in an education unit, a learning evaluation is always carried out. One form of learning evaluation in schools is to carry out final semester exams. This study aims to determine the quality of online business lesson items for class XII SMK Sunan Drajat Lamongan in the odd semester 2017/2018 academic year in terms of validity, reliability, difficulty level and difference tests. This quantitative research is based on data from 21 student answer sheets from 25 multiple choice questions. The use of SPSS and Anates V4 software was used to measure the level of validity, reliability, difficulty level and item difference. The results showed that the validity value obtained was 15 items (60%) were declared invalid and 10 items (40%) were declared valid. Reliability of the items with a Cronbach Alpha value of 0.640> 0.6, which means that the instrument of the 25 items was declared reliable. The level of difficulty of the tested items obtained 5 items in the very easy category, 10 items in the easy category and 10 items in the moderate category. Of the 25 items, 8 items (32%) are good, 7 (28%) are sufficient and 10 (40%) are bad